GAMBARAN POLA KONSUMSI PANGAN DENGAN PENDEKATAN POLA PANGAN HARAPAN (PPH) PADA KELUARGA PEROKOK DI KECAMATAN BERASTAGI - Afriani Christina KS; Etty Sudaryati; Evawani Yunita Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACT Smoking habits in the family can affect the quantity and quality of food consumed by the family. Dangers of cigarette smoke can reduce appetite, food expenditure, nutritional status families, and cause disease. This study is a descriptive survey with the aim to reveal the pattern of food consumption with Desirable Dietary Pattern (DDP) approach  in smoking households in Berastagi District. The population in this study is the entire family that has one or more family members who smoke and have toddlers or pregnant women in Berastagi District that is 2410 families. The sample is a portion of the population which selected by using the cluster method, that is 100 families. Primary data collection use Food List and Food Frequency form. The results show that mostly smokers families  do not consume appropriate food in accordance with the food classification in Desirable Dietary Pattern (DDP). Low energy consumption of smokers families can see from 100 families only 34,0% consume adequate energy (≥AKERK), whereas for 66,0% is inadequate (<AKERK). And for protein, it’s only 78,0% consume adequate protein (≥ AKRPK), whereas for 28,0% is inadequate (<AKRPK). Food frequency of family smokers dominated by grain food groups while others rarely consumed. Average DDP scores of smokers families for Berastagi District is low, that is 61,15. Only 3,0% of 100 families is categorized high named golden triangle  (≥87). Based on this research, it is expected to have good cooperation in cross sectors to provide nutrition counseling, health, and the dangers of smoking for people to increase consumption of nutritious and balanced food. The public to use their own bare land for family food supplies. Keywords: food consumption patterns, DDP score, smoker families